2013
DOI: 10.1016/j.virol.2013.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Host cell tropism mediated by Australian bat lyssavirus envelope glycoproteins

Abstract: Australian bat lyssavirus (ABLV) is a rhabdovirus of the lyssavirus genus capable of causing fatal rabies-like encephalitis in humans. There are two variants of ABLV, one circulating in pteropid fruit bats and another in insectivorous bats. Three fatal human cases of ABLV infection have been reported with the third case in 2013. Importantly, two equine cases also arose in 2013; the first occurrence of ABLV in a species other than bats or humans. We examined the host cell entry of ABLV, characterizing its tropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…One such cell line, CHOK1 cells, were previously reported to be highly permissive to the CVS-11 strain of RABV [29], suggesting that ABLV and RABV may utilize alternate receptors for host cell entry. We confirmed the high susceptibility of CHOK1 cells to RABV CVS-11 G-mediated viral entry and also found that PCI-13 cells, another ABLV resistant line, were also highly permissive to RABV G-mediated entry [30]. Both CHOK1 and PCI-13 cells were shown to express the proposed RABV protein receptors nAchR and NCAM, indicating that nAchR and NCAM are not sufficient to allow host cell entry of ABLV.…”
Section: Lyssavirus Entrysupporting
confidence: 66%
See 1 more Smart Citation
“…One such cell line, CHOK1 cells, were previously reported to be highly permissive to the CVS-11 strain of RABV [29], suggesting that ABLV and RABV may utilize alternate receptors for host cell entry. We confirmed the high susceptibility of CHOK1 cells to RABV CVS-11 G-mediated viral entry and also found that PCI-13 cells, another ABLV resistant line, were also highly permissive to RABV G-mediated entry [30]. Both CHOK1 and PCI-13 cells were shown to express the proposed RABV protein receptors nAchR and NCAM, indicating that nAchR and NCAM are not sufficient to allow host cell entry of ABLV.…”
Section: Lyssavirus Entrysupporting
confidence: 66%
“…Interestingly, we found that the same is true for Saccolaimus and Pteropus variants of ABLV which showed a 6 to 45-fold difference in infectivity in three different cell lines derived from three different species [30]. These recent findings highlight the need for further research on lyssavirus entry.…”
Section: Lyssavirus Entrymentioning
confidence: 64%
“…Contact between domestic dogs and ABLV infected bats has been reported previously [27], and our data indicate occasional pet animal-bat interactions (dogs/cats attacking bats on 62 occasions). Molecular studies on lyssavirus host cell entry mechanisms have found that ABLV host cell receptor is broadly conserved among mammals [28], indicating these animals are likely to be susceptible to ABLV infection. Future research is needed to better understand the potential transmission of ABLV from bats to domestic animals and implications for public health.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant maxGFP expressing vesicular stomatitis viruses (rVSV) that express ABLV G, Ebola Zaire GP, and VSV (Indiana) G glycoproteins have been previously described [6]. VSVΔG-G*-RFP pseudovirus stocks were kindly provided by Michael Whitt (University of Tennessee).…”
Section: Methodsmentioning
confidence: 99%